Information model for the enhancement of human intelligence for the period 2009-2020 - Vidučić, Vinko (Array, 2009)
This paper analyses the "Global information model for the enhancement of human intelligence and memory, for the period 2008 – 2020." The analysis and evaluation of the respective model variables, as well as the resulting growth rates have been aimed at a scientific formulation of the research results, using the most relevant theoretical principles of synergistic relations between human intelligence and memory. The basic scientific hypothesis has been proven through the direct growth rates of the given model variables: with scientific insights into synergistic relations between human intelligence and memory, it is possible to propose a new "Global information model for the enhancement of human intelligence and memory, for the period 2008 – 2020."